Viability study on executive bus service: among the existing express bus commuters / Basimah Ishak - Basimah, Ishak (1993)
Executive Bus Service is a new phenomena In transportation industry in Malaysia. From time to time the operator will improve and provide better services to fulfill the passenger's satisfaction. The implementation of this service, indicates a positive development In transportation industry especially in road transport. The first chapter of this thesis will highlight on the background of the study, the objectives, the scopes and limitations and also the methodology that will be used through out the thesis. company. The second chapter Is about the Executive Bus. The writer would also discuss the differences between the Executive Bus and existing express bus service (refer to the Ekspres Nasional buses). In chapter three, the writer will highlight on SISB. The writer will discuss the mission and objectives of this company, the target market , the characteristics of Executive Bus and other important imformation of this In chapter four, the writer will discuss about ENB and the Engineering Division, ENB.